D.E is
"(2t\\sin(y)+e^ty^3)dt+(t^2\\cos(y)+3y^2e^t)dy=0"Now .divide both side of the above equation by "dt" ,thus we get
"(2t\\sin(y)+e^ty^3)+(t^2\\cos(y)+3y^2e^t)\\frac{dy}{dt}=0\\\\\n\\implies 2t\\sin(y)+t^2\\cos(y)\\frac{dy}{dt}+e^ty^3+3y^2e^t\\frac{dy}{dt}=0\\\\"Note that
"2t\\sin(y)+t^2\\cos(y)\\frac{dy}{dt}=\\frac{d}{dt}(t^2\\sin(y))\\\\\ne^ty^3+3y^2e^t\\frac{dy}{dt}=\\frac{d}{dt}(y^3e^t)"Thus,
"2t\\sin(y)+t^2\\cos(y)\\frac{dy}{dt}+e^ty^3+3y^2e^t\\frac{dy}{dt}=0\\\\\\implies \n\\frac{d}{dt}(t^2\\sin(y)+y^3e^t)=0\\\\\n\\implies \\int d(t^2\\sin(y)+y^3e^t)=\\int0dt\\\\\n\\implies t^2\\sin(y)+y^3e^t=c"
Comments
Leave a comment